EFFECTS OF FERTILIZER APPLICATION AND SPACINGS ON GROWTH PERFORMANCES OF SOME ACACIAS - Wasuwanich, Pisal (วารสารวนศาสตร์ไทย, 2022)
This paper was a part of the study on growth/yield at Sri Thong Experiment Station, Thai-Japan Project (Sakaerat) and Huai Tha Experiment Station to study effects of fertilizer application and spacings on growth performances (height and diameter) of A. auriculaeformis, A. aulacocarpa, A. crassicarpa and A. leptocarpa. However, only 2 species were sclected to plant at each experimental site according to their better growth performances in the ACIAR specics trials in 1985, 1986 and 1987 in Thailand. Effect of the fertilizer application on height and diameter growths was minimal and not consistant. There was no significant differences in the fertilizer application on height and diameter growths at all sites and in all species at 12 and 24 months, except at Sai Thong where only the fertilizer application was significantly different in both height and DBH growths of A. auriculaeformis at 12 monts. However, the differences disappeared at 30 months. There was no significant difference in spacings on height and diameter growths at all experimental sites and in all species at 12 months, on height and diameter growths at Sakacrat at 24 monts, and on height at Huai Tha at 24 months and at Sai Thong at 30 months. However, the spacings indicated significant differences in DBH of A. auriculaeformis and A. crassicarpa at Sai Thong at 30 months and in DGL of A. aulacocarpa and A. leptocarpa at Huai Tha at 24 months. Species tested at both sites had larger diameters in 2 x 4 spacing than in other spacings. No interaction between fertilizer application and spacings was significantly observed at 12 and 24 or 30 months at all sites and in all species.